ATLASGAL – evolutionary trends in high-mass star formation. Issue 3 (4th December 2021) - Urquhart, J S; Wells, M R A; Pillai, T; Leurini, S; Giannetti, A; Moore, T J T; Thompson, M A; Figura, C; Colombo, D; Yang, A Y; König, C; Wyrowski, F; et al.
ABSTRACT: ATLASGAL is an 870-µm dust survey of 420 deg 2 the inner Galactic plane and has been used to identify ∼10 000 dense molecular clumps. Dedicated follow-up observations and complementary surveys are used to characterize the physical properties of these clumps, map their Galactic distribution, and investigate the evolutionary sequence for high-mass star formation. The analysis of the ATLASGAL data is ongoing: We present an up-to-date version of the catalogue. We have classified 5007 clumps into four evolutionary stages (quiescent, protostellar, young stellar objects and H ii regions) and find similar numbers of clumps in each stage, suggesting a similar lifetime. The luminosity-to-mass ( L bol / M fwhm ) ratio curve shows a smooth distribution with no significant kinks or discontinuities when compared to the mean values for evolutionary stages indicating that the star formation process is continuous and that the observational stages do not represent fundamentally different stages or changes in the physical mechanisms involved. We compare the evolutionary sample with other star formation tracers (methanol and water masers, extended green objects and molecular outflows) and find that the association rates with these increases as a function of evolutionary stage, confirming that our classification is reliable. This also reveals a high association rate between quiescent sources and molecular outflows, revealing that outflows are the earliest indication that star formation has begun and that star formation is already ongoing in many of the clumps that are dark even at 70 µm.